2019
DOI: 10.1109/jiot.2019.2912022
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Network Vulnerability Analysis of Industrial Internet of Things

Abstract: From 2012 to 2015, her research concerned performance improvement of communication networks. Since 2015, she has been a Graduate Research Assistant with Washington University in St. Louis. Her current research interests include utilizing machine learning and deep learning for network security of the Industrial Internet of Things, Internet of Things, machine learning, cyber-security, secure computer networks, and wireless communications. Marcio A. Teixeira (M'18-SM'18) received the M.Sc. degree in computer scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
172
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(174 citation statements)
references
References 24 publications
0
172
0
2
Order By: Relevance
“…Conventional security methods are not sufficient as industrial networks are foreseen to be frequently upgraded and their topologies are subject to changes. In this direction, adopting AI-based approaches is indispensable, in order to significantly enhance the network intelligence and security of industrial processes [ 54 ]. Towards this end, the AI algorithms can identify small anomalies in data flows from various sensors, which are the source of industrial data, thus constituting an important enhancement of the cybersecurity within factory halls.…”
Section: Realization Aspects Of Ai-based System Elementsmentioning
confidence: 99%
“…Conventional security methods are not sufficient as industrial networks are foreseen to be frequently upgraded and their topologies are subject to changes. In this direction, adopting AI-based approaches is indispensable, in order to significantly enhance the network intelligence and security of industrial processes [ 54 ]. Towards this end, the AI algorithms can identify small anomalies in data flows from various sensors, which are the source of industrial data, thus constituting an important enhancement of the cybersecurity within factory halls.…”
Section: Realization Aspects Of Ai-based System Elementsmentioning
confidence: 99%
“…Zolanvari, Teixeira, Gupta, Khan, and Jain (2019) uses machine learning based anomaly detection in industrial internet of things and thus provides security to the infrastructure. Zolanvari et al (2019) demonstrates their model by deploying backdoor, command injection and structured query language injection attacks and proved their machine learning model performed well against anomalies.…”
Section: Literature Surveymentioning
confidence: 99%
“…These works obtain the data from different data sources such as logs or system sensors, which allows them to perform analysis for intrusion detection [22] or vulnerability analysis [23]. There are, nonetheless, some proposals for using machine learning to support an incident response process; for example, in [24] the authors propose a system that uses a supervised learning model to analyze different types of attacks, or in [25], where the authors use machine learning models to categorize whether a reported event is an incident or not. None of these pieces of work follows a methodological approach, however, nor do they focus on ensuring the operation of the big data environment itself.…”
Section: Related Workmentioning
confidence: 99%
“…Big data with blockchain [16,17] Big data operation monitor [18,19] Machine learning for security [20][21][22][23] Machine learning for incident response [24,25]…”
Section: Machine Learningmentioning
confidence: 99%